Instruction to the Double: a promising socio-constructivist method for medical education - Durand-Moreau, Quentin; Abadie, Pascale; Bowen, François; Fernandez, Nicolas (Canadian Medical Education Journal, 2025)
Instruction to the Double is a method used in work psychology. Its key interest is that it bridges the gap between real and prescribed work. From a theoretical standpoint, Instruction to the Double is embedded in Vygotskian socio-constructivism. It aims at developing the learners’ power to act. In practice, learners select a practical situation from their work experience and participate in an interview where the learner presents step-by-step instructions to a facilitator as to how intervene in that situation. The facilitator must focus on the how, rather than the why. Learners subsequently access the recorded interview and transcript. The method’s potential for development resides in surprising learners with the discrepancy between what they think they do, and what they say they do. Such discrepancy facilitates learner’s development of their power to act. Instruction to the Double can be a promising learning method in medical education, especially for post-graduate and continuing professional development learners.